2008
DOI: 10.1158/0008-5472.can-07-3177
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3ζ Down-regulates p53 in Mammary Epithelial Cells and Confers Luminal Filling

Abstract: Recent progress in diagnostic tools allows many breast cancers to be detected at an early preinvasive stage. Thus, a better understanding of the molecular basis of early breast cancer progression is essential. Previously, we discovered that 14-3-3Z is overexpressed in >40% of advanced breast cancers, and this overexpression predicts poor patient survival. Here, we examined at what stage of breast disease 14-3-3Z overexpression occurs, and we found that increased expression of 14-3-3Z begins at atypical ductal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
99
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 42 publications
11
99
0
Order By: Relevance
“…As such, these proteins might have the potential to be putative breast cancer markers. As expected, some well-known breast cancer markers, such as 14-3-3 proteins (Danes et al, 2008), annexins (Cao et al, 2008a), calmodulin (Gallo et al, 2008), anterior gradient homolog 2 (AGR-2) (Zweitzig et al, 2007;Fritzsche et al, 2006), Galectin-1 (Jung et al, 2007) and Rho-associated protein kinase-2 (ROCK2) (Fu et al, 2008b), were also identified in this 2D-DIGE experiment, lending credence to the reliability of early phase biomarker detection using this experimental strategy. Fig.…”
Section: D-dige and Maldi-tof Ms Analysis Of Total Intracellular Prosupporting
confidence: 79%
“…As such, these proteins might have the potential to be putative breast cancer markers. As expected, some well-known breast cancer markers, such as 14-3-3 proteins (Danes et al, 2008), annexins (Cao et al, 2008a), calmodulin (Gallo et al, 2008), anterior gradient homolog 2 (AGR-2) (Zweitzig et al, 2007;Fritzsche et al, 2006), Galectin-1 (Jung et al, 2007) and Rho-associated protein kinase-2 (ROCK2) (Fu et al, 2008b), were also identified in this 2D-DIGE experiment, lending credence to the reliability of early phase biomarker detection using this experimental strategy. Fig.…”
Section: D-dige and Maldi-tof Ms Analysis Of Total Intracellular Prosupporting
confidence: 79%
“…11 Several studies have shown that activation of oncogenic growth factor receptor (GFR) signalling can induce aberrant filling of the luminal space. 3,5,12 Similar effects have been observed upon inhibition of pro-apoptotic players such as BIM, BMF and p53, 5,6,13 indicating that either GFR activation and/or the inhibition of distal pro-apoptotic effectors underlie anchorage independence of breast cancer cells. Indeed, mutations in the PI3K and p53 pathway are among the most observed mutations in epithelial cancers, including breast cancer.…”
mentioning
confidence: 67%
“…This demand function was used as the objective function for flux balance analysis analysis. The growth rates for different substrate uptake rates were computed based on minimal media (see "Experimental Procedures" for simulation conditions) and compared with the experimental results of aerobic chemostat cultivation (13,23). Under these conditions, the model used the caa 3 terminal oxidase activity as part of the optimal flux distribution and resulted in higher in silico growth rates than experimental results (Fig.…”
Section: Resultsmentioning
confidence: 99%